Did Akhenaten’s Founding of Akhetaten Cause a Malaria Epidemic? - Sabbahy, Lisa.
This paper presents and discusses evidence for changes in the environment that would have taken place at the site of Amarna, ancient Akhetaten, during the rapid building and populating of the city in the reign of King Akhenaten. The evidence suggests that the effect of the founding of this city, with all the consequences of a changed environment on both sides of the river, could have been responsible for a malaria epidemic. This scenario is backed up by the high prevalence of signs of malaria in the skeletal material from Amarna, as well as in the short-lived history of the city, which was deserted after about fifteen years. doi: http://dx.doi.org/10.5913/jarce.56.2020.a011